(untitled) (ENTHYMEMA, 2011)
From the 13th to the 20th of June, 2010, many notable Dostoevsky’s scholars have met in Naples for the XIVth International Dostoevsky Symposium Dostoevsky. Philosophical Mind, Writer’s Eye, a conference organized by the International Dostoevsky Society.